Iraqi clans and their role in political and civilized integration in Iraq until the end of the monarchy in 1958 (Journal of the College of Basic Education, 2022)
The Iraqi society is one of the organically and socially interconnected societies due to the family rapprochement between its members, brotherhood ties, peaceful coexistence, and cultural and civilizational rapprochement, which were reinforced by similar values of clan systems and inherited tribal customs, which was positively reflected on achieving social peace and controlling the behavior of individuals according to standards stemming from the social and cultural reality. In Iraq and reinforced by the growing political role of the clan represented by its sheikh in the modern Iraqi state and its initial integration with the civil role adopted by the emerging parties after the formation of the Iraqi government in 1921.